Corporate social innovation in East African Breweries Ltd. - (:unkn) unknown (Fundacio ESADE, 2015)
In December 2003, East African Breweries Ltd(EABL) launched a low-cost beer named Senator targeted at low-income consumers in Kenya. The decision was based on the realization that a significant portion of Kenyan alcohol market was divided between traditional brews and illicit liquors. These brews and liquors were leaving behind a trail of health problems on their consumers. The government of Kenya had requested EABL's help in solving this problem. Diageo, the london-based brewing giant, was EABL's main shareholder. EABL management had convinced Diageo that a low-cost beer was an appropriate response to the decline of EABL's market share while simultaneously being a socially responsible investment. However, a six-month post-lauch survey done in May 2004 had shown that senator was not selling as well had been projected. Further, the survey found that some EABL patrons were trading down from the premium brands like tusker to senator. In June 2004, Gerald Mahinda, EABL group managing director had only one question for Lemmy Mutahi, EABL marketing manager for emerging brands:how to make senator a sustainable social product innovation for EABL and by extension Diageo.
This material belongs to Fundacio ESADE. Distributed by ecch, UK and USA
In December 2003, East African Breweries Ltd(EABL) launched a low-cost beer named Senator targeted at low-income consumers in Kenya. The decision was based on the realization that a significant portion of Kenyan alcohol market was divided between traditional brews and illicit liquors. These brews and liquors were leaving behind a trail of health problems on their consumers. The government of Kenya had requested EABL's help in solving this problem. Diageo, the london-based brewing giant, was EABL's main shareholder. EABL management had convinced Diageo that a low-cost beer was an appropriate response to the decline of EABL's market share while simultaneously being a socially responsible investment. However, a six-month post-lauch survey done in May 2004 had shown that senator was not selling as well had been projected. Further, the survey found that some EABL patrons were trading down from the premium brands like tusker to senator. In June 2004, Gerald Mahinda, EABL group managing director had only one question for Lemmy Mutahi, EABL marketing manager for emerging brands:how to make senator a sustainable social product innovation for EABL and by extension Diageo.
Keywords: Innovation; corporate,East African Breweries; Senator